Factors Associated with Motorcycle Risk Behavior among Thai University Students, Khon Kaen - Yudha Puratmaja; Lina Handayani; Kartika Setyaningsih Sunardi (Institute of Advanced Engineering and Science, 2017)
The aim of this research was to assess motorcycle risk behavior (MRB) among Thai students in Khon Kaen University. The research used a cross sectional study. Fifty Thai students recruited using purposive sample technique and the chi-square test was used to analyze relationship between characteristic associated with MRB. The most common MRB were making U-turn (38%), sometimes driving above the speed limit (36%), driving with more than two passanger (48%) and sometimes not wearing helmet (36%). The result showed that sex and riding history associated with MRB (Psex < 0.05; Priding history < 0.05). Sex and riding history were significantly associated with MRB. Improving knowledge is important to decrease risky motorcycle driving behavior. Additionally, the need to provide intervention programs, promotion, and awareness related to student’s safety riding behavior could be recommended, from this information.